Successful radical surgical resection of initially unresectable intrahepatic cholangiocarcinoma by downsizing chemotherapy with gemcitabine plus cisplatin: a case report - Ryosuke Takayanagi; Shigetsugu Takano; Kensuke Sugiura; Hideyuki Yoshitomi; Katsunori Furukawa; Tsukasa Takayashiki; Satoshi Kuboki; Atsushi Kato; Masaru Miyazaki; Masayuki Ohtsuka (Surgical Case Reports)
Abstract Background Intrahepatic cholangiocarcinoma (ICC) is a subtype of biliary tract cancer (BTC). Recently, downsizing chemotherapy has been applied to initially unresectable BTCs, including ICC. Case presentation We report a case of liver resection in a 23-year-old woman who was diagnosed with initially unresectable ICC attached to the inferior vena cava, with portal vein (PV) cavernous transformation. Positron emission tomography (PET) showed fluorodeoxyglucose (FDG) uptake in the para-aortic lymph nodes. Upon using downsizing chemotherapy (the combination of gemcitabine [GEM] and cisplatin [CDDP]), the size of tumor reduced by 55% and FDG uptake in the para-aortic lymph node metastases disappeared. A right hemihepatectomy was performed, along with dissection of lymph nodes, including the para-aortic lymph nodes. The PV cavernous transformation was preserved to maintain collateral flow as much as possible, as it was considered to originate from a congenital anomaly. Pathological examination revealed that R0 resection was performed and that there were no viable neoplastic cells remaining in the para-aortic lymph nodes. The patient is alive at 31 months after initial treatment, with a local recurrence. Conclusion Downsizing chemotherapy with GEM plus CDDP followed by radical surgical resection is an attractive treatment for initially unresectable BTC.